Safety and importance of colonoscopy in nonagenarians. Issue 3 (11th November 2021) - Sung, Kuan-I; Wang, Yen-Po; Chang, Tien-En; Wang, Huann-Sheng; Jiang, Jeng-Kai; Luo, Jiing-Chyuan; Lee, Fa-Yauh; Hou, Ming-Chih; Lu, Ching-Liang
Abstract : Background: With the growth of the aging population, the need for colonoscopies in nonagenarians is rising. However, few data on colonoscopies in extremely elderly individuals are available. To better acknowledge the role of colonoscopies in this specific group of patients, we conducted this study to evaluate the safety and clinical impact of colonoscopy in nonagenarian patients. Methods: We performed a retrospective cohort study comparing nonagenarians who received colonoscopy in a tertiary medical center in Taiwan in 2016 with 76- to 80-year-old patients (relatively elderly patients) who were 1:1 propensity score matched by sex as the control subjects. The postcolonoscopy 30-day adverse events, mortality, and long-term survival were recorded. Results: A total of 137 nonagenarians and 137 relatively elderly patients were included. The nonagenarians receiving colonoscopy were more likely to be hospitalized (40.1% vs 19.7%, p < 0.001), and the adjusted colonoscopy completion rates were comparable in both groups (92.0% vs 97.1%, p = 0.063). The overall adverse event rate and postcolonoscopy 30-day mortality rates were low in both groups (2.9% vs 1.5%, p = 0.409 and 2.2% vs 1.5%, p = 0.652, respectively). A total of 18.2% of the nonagenarians were diagnosed with advanced neoplasia. Among the nonagenarians diagnosed with colorectal cancer, the patients receiving surgery had a significantly lower risk of death than the patients receiving conservative management (hazards ratio 0.1044, 0.01275–0.8529, p = 0.0352). Conclusion: Colonoscopy in patients older than 90 years is generally safe. Colonoscopy findings that led to surgery in nonagenarians diagnosed with colorectal cancer were associated with survival benefits.